Pengaruh Preheating Terhadap Nilai Kekerasan Pada Pengelasan Baja Hardok 450 Menggunakan Metode Pengelasan Smaw - nurkolis, dwi; Hidayat, Amri; Aldrin, Aldrin; Dzil Ikram, Fadhli (Jurnal GEAR (Energi, Perancangan, Manufaktur & Material), 2024)
Preheating is carried out by heating around the welding point, before welding begins, which is called the preheating temperature. Stabilizing the sample temperature before welding is intended to carry out preheating to prevent damage and defects during and after welding. The aim of this research is to determine the effect of preheating temperature on the hardness value of SMAW welding results on the hardness test on Hardok 450 steel. The welding carried out was the SMAW method on Hardok 450 steel using a 60? V seam connection. The preating temperatures used in this research were 200?C, 300?C and 400?C. The results of SMAW welding are subjected to hardness testing. From the results of the hardness testing, the hardness value increases as the preheating temperature increases. The lowest hardness value was obtained at a temperature of 200?C with an average hardness value of 68.2 HRC in the HAZ (Heat Affected Zone) area and an average value for weld metal of 64.6 HRC. Meanwhile, the highest hardness value was obtained at a temperature of 400?C, the average hardness value was 77.8 HRC in the HAZ area, while the hardness value for weld metal was 67.3 HRC